Who is stocking privately produced fish? A look at the customers of the private, recreation-based aquaculture industry in Colorado - Deisenroth, Daniel B., author; Bond, Craig A., author; Geleta, Soloman, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2012)
The purpose of this factsheet is to document the expenditure patterns, preferences and demographic statistics of a variety of first point-of-sale customers of Aquaculture Suppliers of Recreational Fish (also known as the ASRF industry). The Department of Agricultural and Resource Economics at Colorado State University administered the project in conjunction with participation of faculty members throughout the Western United States (West of the Colorado-Kansas border).
April 2012.
Keywords: fishery managers; privately stocked fisheries; ASRF customer; anglers; Colorado Division of Wildlife